Child-Friendly Education Model and Islamic Character Development in Madrasah Ibtidaiyah Cendekia Pekanbaru - Mursal Mursal; Muhammad Hafiz; Syamsul Rizal; Rahmad Fauzi Lubis (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study investigated child-friendly education model in shaping student character within Madrasah Ibtidaiyah Pekanbaru, addressing a gap in empirical evidence for its direct impact in Indonesian Islamic schools. Employing a quasi-experimental design with a pre-test post-test non-equivalent control group, 58 Grade 4 and 5 students participated. Data were collected via observation rubrics and student self-assessment questionnaires, validated by experts and pilot-tested for reliability, alongside qualitative teacher interviews. Quantitative data were analyzed using SPSS 26.0, primarily via ANCOVA to compare post-test scores while controlling for pre-test variations. The findings robustly demonstrate the model's significant positive impact on all measured character traits: honesty (F(1, 55) = 18.23, p < .001), responsibility (F(1, 55) = 22.87, p < .001), discipline (F(1, 55) = 15.67, p < .001), empathy (F(1, 55) = 10.12, p = .002), and religious values (F(1, 55) = 9.88, p = .003). Qualitative data from teacher interviews corroborated these improvements, highlighting enhanced student engagement, social cohesion, and self-regulation. While limited to a single institution, these results provide compelling evidence that a child-friendly approach effectively fosters comprehensive character development in madrasahs, encouraging its broader adoption and further longitudinal research across diverse educational contexts.